Performance evaluation of single-ended disturb-free CNTFET-based multi-Vt SRAM. (August 2019) - Patel, Pramod Kumar; Malik, M.M.; Gupta, Tarun K.
Abstract: We propose a single-ended disturb-free carbon nanotube field effect transistor (CNFET) based stable nine transistors (9T) SRAM cell using multi-threshold (multi-Vt) technology. Simulations of the CNFET 9T SRAM cell, using a CNFET HSPICE model, have shown advantages over the conventional Si-CMOS cell in terms of leakage power consumption, dynamic power consumption, stability, and delay. Due to higher carrier mobility and high ION /IOFF ratio makes the CNFET devices suitable for high-speed nanoelectronics applications. The disturb-free architecture and bit interleaving approach provide error-free operations at the low supply voltage. The proposed SRAM cell implementation for low leakage 16 nm CNFET technologies provides the possibility of high integration density which also significantly reduces 3.2 × power consumptions as compared to the conventional cell. The multi-threshold technology is capable of improving simultaneously the leakage current and dynamic power consumption. The proposed SRAM architecture is implemented with write-assist, adaptive supply voltage scaling and the impact of geometrical liability.